AN ANALYSIS OF CODE SWITCHING USED BY ENGLISH TEACHER BASED ON GENDER INEQUALITY - Chotibul Umam; Dita Sukawati; Fadilla Oktaviana (Journal of English Language Teaching and Literature (JELTL), 2019)
In this research, the writer was aimed to find out the types of code switching that used by English teacher based on gender inequality and the reasons of using code switching that used by English teacher based on gender inequality. The writer was conducted case study in qualitative method. In collecting the data, the writer used observation by using video recording and interview. The result of the research shows that the writer found three types from each teacher based on gender inequality by observation. The types are inter-sentential, intra-sentential and tag switching. In the other hand, each types that used by English teacher based on gender inequality was made in number percentages, for female English teacher are inter sentential code switching 54%, intra sentential code switching 38% and tag switching 8%. Moreover, for male English teacher are inter sentential code switching 42%, intra sentential code switching 41% and tag switching 18%. In the other words, interview was used to find out the reasons that used by English teacher based on gender inequality. The reasons are talking about particular topic, repetition, Interjection and Raising status.